6 The hidden co-worker: research revealing unmet support needs in carers of people with dementia who receive cancer treatment. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Hopkinson, J; King, M; Milton, R
Abstract : Background: Internationally there is a growing population of elderly people. Cancer and dementia are diseases primarily of old age. An increasing number of people will face the challenge of comorbid dementia and cancer. Patients with dementia are diagnosed with cancer at a later stage of disease, receive less treatment and have poor survival compared to patients without dementia. The reasons are unknown. In part, because there has been no research investigating how the cancer team manage the support needs of people with dementia. Method: Our research was of case study design. Data was collected using ethnographic methods. Observation was of the clinical management of 33 people with dementia and/or memory problems in four clinics at a cancer centre. A sub-set of ten clinical consultations were recorded and seven patients were interviewed, six accompanied by a carer. This paper will report cross-case thematic analysis of findings relating to dementia carers. Results: Clinicians rely on patient/carer disclosure to identify patients with memory problems, as memory health is not documented in cancer records. Carers facilitate communication between cancer clinician and patient. They typically elect not to disclose memory problems. This has implications for safe and effective treatment. The education and support needs of carers go unrecognised, with just one example in our data of a clinician talking with the carer about how to manage the behavioural and psychological symptoms of dementia if exacerbated by a new pain medication. Conclusion: This is the first research to evidence dementia carers are hidden coworkers in the cancer team. They facilitate successful cancer management, yet their support needs are largely unrecognised. Training in dementia care is available to cancer clinicians. This should include advice on how to identify and support individuals with memory problems during treatment and recognise then respond to the needs of their carer.